Learning and Memory in an Animal Model of Longevity: The Ames Dwarf Mice - P. Austin, David; N. Weatherly, Jeffrey (Journal of Endocrinology and Hormones, 2025)
The Ames dwarf mice have a recessive mutation of the PROP-1 gene that produces hereditary dwarfism. The abnormality is responsible for an anterior-pituitary deficiency that results in a substantial reduction of growth hormone, thyroid-stimulating hormone, and prolactin. These mice are smaller in size than their normal siblings but live approximately twice as long. The normal siblings do not have the mutation, and therefore still have the typical levels of the three hormones. The purpose of the present research was to determine if the reduced hormones in the Ames dwarf mice affected their ability to learn and delayed the age-related loss of memory. In general, the hypotheses proposed indicate that there will be no significant differences on the tasks in regards to the genotype or the age of the mice. These hypotheses would support previous research and suggest a delay in the age-related loss of memory and the ability to learn in the Ames dwarf mice. Learning was assessed using a matching-to-sample procedure, while memory was evaluated using a modified radial-arm procedure. Generally, the age of the animals had little to do with their performance on any of the tasks. Taken together, the overall results showed no significant differences in accuracy between any of the groups of mice or a behavioral decline as the mice age. The present results are consistent with the theory of a delayed age-related behavioral decline in the Ames dwarf mice.
Keywords: anterior pituitary; hormonal effects; aging; learning; memory; dwarf mouse